Highly stable 3D porous HMOF with enhanced catalysis and fine color regulation by the combination of d- and p-ions when compared with those of its monometallic MOFs - Liu, Jiao; Zhao, Ying; Dang, Li-Long; Yang, Guoping; Ma, Lu-Fang; Li, Dong-Sheng; Wang, Yaoyu (Chemical communications (Cambridge, England), 2020)
In this study, two new monometallic organic frameworks (MOFs), namely {[Zn 1.5 L(NMP)(H 2 O)]·H 2 O} n ( 1 ) and {[Pb 2 L 2 (H 2 O) 2 ]·H 2 O} n ( 2 ), were synthesized for the first time by a new bifunctional N,O-containing 2-(1 H -tetrazol-5-yl)terephthalic acid (H 2 L) ligand. Then, based on the HSAB principle, another porous Pb-Zn heterometallic organic framework (HMOF), namely {[PbZn 0.5 L(H 2 O)]·0.5NMP·H 2 O} n ( 3 ), was successfully obtained for the first time by combining Pb( ii ) and Zn( ii ) ions with H 2 L. The MOFs 1 and 2 are 3D densely packed frameworks, whereas the HMOF 3 is a porous 3D framework (28.9% porosity) with 1D open channels modified by Lewis basic sites (exposed N atoms) and Lewis acidic sites (unsaturated bimetallic sites). The HMOF 3 has a strong boiling water/acid-base resistance (pH = 2-12) and shows an enhanced high-efficiency catalytic effect for CO 2 conversion (98%) under ambient temperature and pressure conditions. In addition, fine color regulations of the MOFs were successfully realized by doping different kinds of metal ions into them. This study aims to provide a new way and field of vision for the construction of HMOFs and their multi-functional materials. Three comparable MOFs were yielded successfully. Among them, the highly stable HMOF is a porous 3D motif with lots of active sites, leading to the enhanced catalysis for CO 2 conversion and fine color regulations of MOFs by doping different ions.